Instantaneous rigor - the challenge of securing an airway in cardiac arrest: a case report - Michal Soták; Tomáš Henlín; Tomáš Tyll (International Journal of Emergency Medicine)
Abstract Cadaveric spasm, also known as instantaneous rigor, is a rare and poorly understood phenomenon characterized by immediate muscle rigidity at the moment of death or cardiac arrest. This can result in severe trismus, making conventional airway management impossible. We present a case of a morbidly obese patient who suffered a sudden cardiac arrest with instantaneous rigor, necessitating an urgent surgical cricothyrotomy. This report underscores the need for early recognition of this condition, rapid decision-making regarding airway management, and the importance of specialized training for emergency physicians, particularly in anatomically challenging scenarios.